Porcine Tracheal Mucosa-Derived Decellularized Patch to Prevent Septal Perforation in a Rabbit Model. Issue 4 (July 2021) - Kim, So Jeong; Jung, Soo Yeon; Lee, Min Ji; Bae, Jung Ho; Kim, Han Su
Background: Nasal septal perforation is caused by bilateral septal mucosal injuries resulting from nasal trauma and septal surgeries. Previous studies have reported that biocompatible materials may be effective for repairing nasal septal perforations. However, they were primarily used for treatment; no study has investigated their use for prevention of nasal septal perforation. Objective: To determine whether porcine tracheal mucosa-derived decellularized patch can prevent the progression of nasal mucosa injuries to septal perforations. Methods: Bilateral nasal septal mucosal defects were surgically induced in 36 rabbits. Silastic sheets were applied bilaterally in all rabbits, and decellularized mucosal patch was applied unilaterally (n = 12) or bilaterally (n = 12) at the defect site in the respective experimental groups. Between 1 and 8 weeks postoperatively, the animals were sacrificed, and their nasal septa were completely removed. The excised septa were examined macroscopically and microscopically (histopathological examinations). Moreover, glycosaminoglycan (GAG) estimations of the septa were performed to evaluate mucosal regeneration and mechanical properties. Results: Septal perforations occurred in 5 animals in the control group (5/12; 42%), 1 in the unilateral group (1/12; 9%), and in none in the bilateral group. Compared with the control group, the experimental groups showed significantly different mucosal and cartilage regeneration. Conclusion: Decellularized porcine tracheal mucosa can prevent mucosal defects from progressing to septal perforation, promote the repair of mucosal defects, and protect the nasal cartilage.